2015
DOI: 10.1080/00224499.2014.993748
|View full text |Cite
|
Sign up to set email alerts
|

Societal Norms Rather Than Sexual Orientation Influence Kin Altruism and Avuncularity in Tribal Urak-Lawoi, Italian, and Spanish Adult Males

Abstract: Homosexual males could balance their low fitness by increasing benefits to relatives either through kin-directed altruism or by avuncularity (altruistic behavior toward the children of siblings). Evidence in support of kin selection and avuncularity includes the fact that homosexuals seem to be more empathic and altruistic than heterosexuals. Other studies have not confirmed behaviors that increase kin altruism in homosexuals. We explored altruistic behavior and avuncularity in a sample of 278 subjects, either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In contradistinction to this kin selection hypothesis for male androphilia, Camperio Ciani, Battaglia, and Liotta (2015) reported that male sexual orientation differences in avuncularity do not exist among the Urak-Lawoi of Ko Lipe 1 , a small island in the Andaman Sea off the southern coast of Thailand. 2 Male androphiles in this population are often transgender, although cisgender male androphiles also exist.…”
mentioning
confidence: 99%
“…In contradistinction to this kin selection hypothesis for male androphilia, Camperio Ciani, Battaglia, and Liotta (2015) reported that male sexual orientation differences in avuncularity do not exist among the Urak-Lawoi of Ko Lipe 1 , a small island in the Andaman Sea off the southern coast of Thailand. 2 Male androphiles in this population are often transgender, although cisgender male androphiles also exist.…”
mentioning
confidence: 99%